2018
DOI: 10.20508/ijrer.v8i4.8342.g7509
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Biodegradable Waste Quality by Drying for exploring the Possibilities of a Potential Renewable Energy Source in Yangon City, Myanmar

Abstract: Biodegradable waste to fuel becomes a potential renewable energy source to gain environmental and economic benefits in the world. To explore the opportunities of a potential renewable energy source from the biodegradable wastes in Yangon city, the study collected 12 different waste samples from the four districts of Yangon and evaluated the composition of the collected wastes. Then, the study assessed their moisture contents by Halogen Moisture Analyzer and dried 23 prepared waste samples (100 grams, 300 grams… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
0
0
Order By: Relevance
“…If such wastes were to be processed to a stable shelf life (20 % to 40 % moisture content), a reasonable amount of moisture has to be removed. Interestingly, such significant moisture removal causes a substantial reduction in the weight and volume of biodegradable waste but increases the energy value (Tun and Juchelkova, 2018). Although some researchers like Polprasert (2007) and Yang et al (2015) have shown considerable interest in biowaste treatment and its benefits relying on the sketchy overview of a range of treatment options, less emphasis was made on the development of a dedicated treatment technology taken into account bio-waste sources, compositions, and characterization.…”
Section: Introductionmentioning
confidence: 99%
“…If such wastes were to be processed to a stable shelf life (20 % to 40 % moisture content), a reasonable amount of moisture has to be removed. Interestingly, such significant moisture removal causes a substantial reduction in the weight and volume of biodegradable waste but increases the energy value (Tun and Juchelkova, 2018). Although some researchers like Polprasert (2007) and Yang et al (2015) have shown considerable interest in biowaste treatment and its benefits relying on the sketchy overview of a range of treatment options, less emphasis was made on the development of a dedicated treatment technology taken into account bio-waste sources, compositions, and characterization.…”
Section: Introductionmentioning
confidence: 99%